Scientific Literacy in the Wild: Using Multimodal Texts in and out of School - Buchholz, Beth A.; Pyles, Damiana Gibbons (The Reading teacher, 2018)
Building a better public education system for our children begins with providing students with real‐world learning experiences from the very beginning. To this end, the authors explored how two kindergarten teachers scaffolded scientific literacy learning using an authentic multimodal text before, during, and after a zoo field trip in ways that fostered the identity of kinder “scientists” along with good literacy skills. From their experiences, public educators can help their students develop strong science knowledge and scientific literacy through rich literacy practices intertwined with learning science content, over a period of time, with multiple, varied, and scaffolded uses of an authentic, multimodal text and paired with authentic, out‐of‐school learning experiences.